Systematic review of the knowledge and attitude about HIV and AIDS among Iranian population - Farideh Mohsenzadeh-ledari; Nahid Akbari; Moniroalsadat Hoseini Tabaqdehi (Babol University of Medical Sciences, 2016)
Background: Inadequate knowledge, negative attitudes are major the hindrances to prevent the spread of human immunodeficiency virus (HIV). The objective of this study was to understand the knowledge and attitude about HIV and AIDS in the Iranian population. Methods: We conducted a systematic review, searching online databases through December 2015 focusing on knowledge and attitudes about HIV and AIDS in Iran.  Inclusion criteria were the cases which aimed to determine the knowledge and attitudes of people, placed in Iran, and conducted in the last fifteen years. After extraction, documentation, specifications of articles and conference were classified in the Endnote software and duplicated cases were removed using this application and new review of the categories. Results: Twenty four articles met criteria.  The knowledge and attitude toward HIV and AIDS were generally found to be  different and varied; these differences can be related to the inconsistency of research tools and applied questionnaires, the content of the questions, number of questions, the difference in the ratings and rankings, as well as sample size, methodology and study type. Conclusion: We conclude that our results will guide the development of population-focused HIV/AIDS knowledge and attitude in Iran, which is to be lacking among both the general public and healthcare.